Integrating Carbon and Environmental Accounting into Sustainability Reporting: A Systematic Literature Review - Ali khalaf Gatea (Generate Digital Publishing, 2025)
Objective: This study aims to analyze the integration of Carbon Accounting (CA) and Environmental Accounting (EA) in Sustainability Reports and their impact on company performance in terms of finance, operations, reputation, and governance, with a focus on the contribution of accounting system harmonization to sustainable value and the challenges of its implementation. Research Design & Methods: Using a Systematic Literature Review (SLR) approach guided by the PRISMA protocol, this study synthesizes findings from 57 peer-reviewed journal articles published between 2002 and 2025 and indexed in Scopus. Findings: The results show a significant upward trend in research related to CA, EA integration, especially after 2020, driven by the adoption of global frameworks such as IFRS S2, GRI Standards, and EU CSRD. Empirical evidence shows that CA/EA integration positively affects corporate performance, especially in large companies with adequate technological and financial capacity. However, challenges remain, including inconsistencies in measurement methods, limitations in data reliability, and reporting practices that are symbolic rather than substantive. Implications & Recommendations: This study emphasizes the importance of global harmonization of sustainability reporting standards, standardization of ESG audits, and strengthening institutional capacity, especially in emerging markets, so that CA/EA data is integrated into strategic management and investment decisions to drive real sustainability transformation. Contribution & Value Added: This study confirms that CA, EA integration unifies financial and environmental accountability, and strengthens the theory and practice of sustainability accounting towards transparency and transition to a low-carbon economy.